Moving image and sound collections for archivists - Cocciolo, Anthony (Chicago, IL The Society of American Archivists, 2017)
"Preservation of and access to moving image and sound records is best advanced by reformatting them to digital formats and engaging in digital preservation of those assets. The eleven chapters of this book are intended to provide solid grounding for general archivists to manage their moving image and sound collections. The first part provides more general practices that can be used regardless of media types, while the second part provides guidance for specific media formats"--Provided by publisher.
Part I. Archival practices for moving image and sound collections -- Appraisal and reappraisal -- Accessioning, arrangement, and description -- Legal and ethical issues -- Digital preservation of digitized and born-digital content -- Access and outreach -- Interactions with moving image and sound producers -- Part II. Format-specific guidance -- Audio collections -- Film collections -- Analog video collections -- Digital video collections -- Complex media -- Epilogue -- Glossary.
Includes index.
Keywords: Digital preservation -- Handbooks, manuals, etc; Film archives -- Handbooks, manuals, etc; Sound archives -- Handbooks, manuals, etc; Archives -- Administration -- Handbooks, manuals, etc